O trabalho como princípio educativo : uma análise do Programa Ensino Médio Inovador (ProEMI) nas escolas públicas de Sorocaba-SP - Dias, Camila Mantovani (2016)
This dissertation is as study on the Ensino Médio Inovador Program (ProEMI), created by the Federal government by ordinance n.º 971, from October 9, 2009. The aim is to debate if this educational policy strengths the early professional development of young students who attend the regular public high schools. Work here is understood as an educational principle, and this study try to investigate the ProEMI in face of the historical and social necessity involved in currently high school education and in the whole youth formation nowadays. The first part focus on the Marxist theoretical and methodological references regarding to the fields of work and education, specially the contribution of the Italian communist Antonio Gramscie. The second part presents a bibliographic review of the history of the high school in Brazil. The objective is to understand how education was structured, its identity and how high school education posited itself in face of the social conflicts and the demands for education and training in the productive world. The second chapter also analyzes the legislation related to the ProEMI, mainly focusing on the first decade of the 21st Century. At the end of this study, the last and final chapter presents a field research at Sorocaba School Board (SP). Three public schools were selected by the grades obtained in the IDESP (Educational Development Index of the State of São Paulo). The research techniques employed were questionnaire and interviews with the school management body and students in the 12th-grade where ProEMI takes place. This study intend to contribute to the unveiling of the public policies for high schools, relating to the necessities involved in this stage of youth training and formation, based on principles of Brazilian theorists in Education, who keep alive the spark of a school for all and of high-quality.